PELATIHAN PENYUSUNAN LAPORAN KEUANGAN DAN PENGEMBANGAN USAHA UNTUK USAHA KECIL (UMKM) DI DESA BARU KECAMATAN PANCUR BATU KABUPATEN DELI SERDANG - Dimita Hemalli Premasari Purba; Rintan Saragih; Mulatua P. Silalahi; Yosephine N. Sembiring; Lamria Sagala; Ivo M. Silitonga; Thomas Sumarsan Goh; Rahel Junita; Duma Rahel Situmorang; Arison Nainggolan; Tri Darma Sipayung; Putri Jesica Sitorus; Rimky Mandala Putra Simanjuntak; Farida Sagala (Jurnal Pengabdian Pada Masyarakat METHABDI, 2021)
A business, both on a large scale and micro, small and medium enterprises (MSMEs) should apply accounting principles in managing financial reports. So that through the implementation of good financial reporting, business owners get information, to be able to formulate strategies and can be used as a basis for decision making. However, not all business owners apply accounting principles due to limited knowledge. The same thing happened to a partner, namely Mr. Sarwo Wibowo (35 years), a business owner in the field of organic fertilizer located in Dusun 2A, Baru Village, Pancur Batu District, Deli Serdang Regency. Since the business was operating, the partner has never made financial records in accordance with accounting standards. One of the impacts is that there is no separation of business finances from household finances. In addition to problems in the field of accounting, partners also experience marketing limitations. Through this Community Service (PKM) activity, the team conducted socialization, training and assistance in the preparation of business bookkeeping to partners as well as exposure to marketing strategies (business development). This training and mentoring aims to assist partners in managing their business so that the accounting and marketing knowledge can later be used as the basis for formulating strategies and making decisions.